2021
DOI: 10.1002/mrm.28727
|View full text |Cite
|
Sign up to set email alerts
|

MRzero ‐ Automated discovery of MRI sequences using supervised learning

Abstract: Magnetic resonance (MR) images can be created noninvasively using only static and dynamic magnetic fields, and radio frequency pulses. MR imaging provides fast image acquisitions which have been clinically feasible only since the discovery of efficient MR sequences, 1-3 ie, time-efficient application of two building blocks: radio frequency pulses and spatial magnetic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…However, the benefits of the CRB‐based experimental design are not tied to any specific reconstruction algorithm, since, the CRB, as an estimation‐theoretic bound, is independent of the reconstruction process. This is generally different from the emerging supervised learning based OED approaches, 22,49,50 which often incorporate a specific reconstruction algorithm into an objective function that performs empirical risk minimization. In practice, we observed that a variety of reconstruction algorithms, including both model‐based 51‐54 and data‐driven methods, 55,56 can benefit from the CRB‐based experimental design, given the SNR benefit such design provides.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of the CRB‐based experimental design are not tied to any specific reconstruction algorithm, since, the CRB, as an estimation‐theoretic bound, is independent of the reconstruction process. This is generally different from the emerging supervised learning based OED approaches, 22,49,50 which often incorporate a specific reconstruction algorithm into an objective function that performs empirical risk minimization. In practice, we observed that a variety of reconstruction algorithms, including both model‐based 51‐54 and data‐driven methods, 55,56 can benefit from the CRB‐based experimental design, given the SNR benefit such design provides.…”
Section: Discussionmentioning
confidence: 99%
“…24 This pulseq-file is then read and played out on the scanner using a vendor-specific interpreter sequence. Although Pulseq is a great tool that enables a flexible implementation of complex sequence patterns, 25 it is complicated to incorporate vendorprovided image reconstruction functions, which are generally proprietary. However, having the source code of a full interpreter sequence at hand, a capsulated interpreter can be included into other existing sequences for imaging readout.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, the number of raw images acquired (N) could be defined as a dynamically optimized parameter. In addition, while the saturation power was limited to not exceed a fixed value for each of the scenarios (Supporting Information Table S1), it could be replaced in the future by a specific absorption rate (SAR) penalty term, incorporated in the cost‐function 58 . Similarly, a penalty term for exceedingly long scan times could be used to further improve SNR/scan‐time balance.…”
Section: Discussionmentioning
confidence: 99%